Co-integration between Electricity Supply and Economic Growth in South Africa - Khobai, Hlalefang; Abel, Sanderson; Le Roux, Pierre (International Journal of Energy Economics and Policy, 2016)
This study probes the short and long run relationship between economic growth, electricity supply, trade openness, electricity prices, employment and capital in South Africa within a multivariate framework. The autoregressive distributed lag bound testing was employed to establish the long run relationship between these variables using data for the period between 1985 and 2014. Major findings of the study include that economic growth, electricity supply, trade openness, electricity prices, employment and capital are co-integrated. Overall, the paper suggests that efficient planning and increased investments in electricity supply industry infrastructure is of essence to solve the problem of electricity supply as this would force the sustainable economic growth in South Africa. Keywords: Electricity Supply, Economic Growth, South Africa JEL Classifications: O13, Q43